Financial Management of Education in Elementary Schools - Ilham Anas; Ardy Abraham; Sri Febrina Ramadhani (Journal of World Science, 2025)
This research is motivated by the importance of education financing management in supporting the continuity of educational activities in elementary schools. This study aims to evaluate the effectiveness of the use of school funding sources, financial responsibility, transparency in financial management, and its impact on the quality of learning in the classroom. This study used a qualitative method with a single case study approach, focusing on the financial management of education in elementary schools in primary schools in the city of Makassar. Data were collected through documentation and interviews. The results showed that financially, primary schools in Makassar did not experience difficulties in obtaining education funds and their use was directed towards the interests of education. The principal worked with the treasurer to manage the funds, which contributed to the implementation of good school programmes. The accountability system in this school demonstrates clear responsibility, with transparency being achieved through the posting of fund utilisation reports on notice boards for public access. The effective use of funds has also been shown to improve the quality of classroom learning, as evidenced by the provision of necessary facilities and infrastructure. In conclusion, the management of education financing in primary schools in Makassar City has followed good procedures, demonstrating strong accountability and transparency, and supporting improvements in the quality of learning.